Design and implementation of a 2D exploration role playing game (B) - Wang, Qiyu (Nanyang Technological University, 2022)
Game Development World Championship (GDWC) is an annual game development competition for game developer teams of different background, ranging from hobby categories for amateur game developers, to studios with 3A titles.